Eve, the Serpent, and the Instructor Beast: Androgyny and Revelation in Gnostic Texts - Troiano, Mariano (Gnosis, 2023)
The present study will focus on a distinctive relationship found in Gnostic mythologems that associates androgyny and revelation. In fact, this connection is present at any of the three levels in which Sethian Gnostic authors structure their cosmology (spiritual, psychic, and material), but it is not usually explicit. In this work, I will center my research on the manifestation of androgyny in the psychic and material levels, with special attention to the latter. My objective is to demonstrate that by taking elements from Christian, Jewish, and Platonic traditions, Gnostic authors give them a new meaning, creating performative myths that construct a new reality. Mental images of an androgynous monster, of an instructive beast that breaks the categories of social normativity, and through which initiates focus their desire and actualize it through gnosis.